2023
DOI: 10.1007/s00122-023-04307-z
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of grain color and tannin content in Chinese sorghum based on whole-genome sequencing

Abstract: Key message Seventy-three QTL related to grain color and tannin content were identified in Chinese sorghum accessions, and a new recessive allelic variant of TAN2 gene was discovered. Abstract Sorghum is mainly used for brewing distilled liquors in China. Since grain tannins play an important role in liquor brewing, accurately understanding the relationship between grain color and tannin content can provide basis for selection standards of tannin s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Sakamoto et al evaluated 329 sorghum germplasms from various origins and identified SNPs potentially associated with seed morphology, including SNP loci S01_50413644, S04_59021202, and S05_9112888 based on multi-traits GWAS [ 13 ]. Zhang et al identified 73 quantitative trait loci (QTL) related to grain color and tannin content in Chinese sorghum accessions, and a new recessive allelic variant of Tannin2 was discovered [ 14 ]. A GWAS conducted on a diverse set of 635 Ethiopian sorghum accessions found variations in loci harboring seed protein genes involved in seed storage, late embryogenesis, and tannin biosynthesis, all of which are associated with sorghum grain mold resistance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sakamoto et al evaluated 329 sorghum germplasms from various origins and identified SNPs potentially associated with seed morphology, including SNP loci S01_50413644, S04_59021202, and S05_9112888 based on multi-traits GWAS [ 13 ]. Zhang et al identified 73 quantitative trait loci (QTL) related to grain color and tannin content in Chinese sorghum accessions, and a new recessive allelic variant of Tannin2 was discovered [ 14 ]. A GWAS conducted on a diverse set of 635 Ethiopian sorghum accessions found variations in loci harboring seed protein genes involved in seed storage, late embryogenesis, and tannin biosynthesis, all of which are associated with sorghum grain mold resistance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, some researchers have conducted in-depth research on the development regulation of sorghum seeds. For example, Tao et al 38 identified 114 candidate genes associated with sorghum seed size, of which 63 showed a signal of purification selection during domestication; Zhang et al 39 identified 73 QTLs related to grain color and tannin content in China sorghum materials through genome-wide association study, and found a new recessive allelic variant of TAN2 gene. Many studies in other plants show that OVATE gene family plays an important role in regulating the development of plant organs and resisting stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, companies that produce light-flavored Baijiu face several challenges, including low yield, limited high-end product options, declining quality, and a stagnant market due to a narrow flavor profile, which have hindered their development ( Yifan et al, 2021 ). Currently, researchers are actively exploring methods to enhance their understanding of light-flavored Baijiu and improve its quality, with research focusing on aspects such as the microbial community structure in light-flavored Daqu, flavor chemistry of light-flavored Baijiu, influence of sorghum varieties on the flavor of light-flavored Baijiu, and the relationship between light-flavored Baijiu and microorganisms ( Liu and Sun, 2018 ; Huang et al, 2020 ; Zhang et al, 2022 ; Xiang et al, 2023 ; Zhang et al, 2023 ). In addition, studies have examined the physicochemical properties of Chinese light-flavored Baijiu during storage and explored ways to improve sorghum varieties for Baijiu production ( Ma et al, 2013 ; Kang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%